2000
DOI: 10.1128/mcb.20.11.4049-4061.2000
|View full text |Cite
|
Sign up to set email alerts
|

Septin-Dependent Assembly of a Cell Cycle-Regulatory Module inSaccharomyces cerevisiae

Abstract: Saccharomyces cerevisiae septin mutants have pleiotropic defects, which include the formation of abnormally elongated buds. This bud morphology results at least in part from a cell cycle delay imposed by the Cdc28p-inhibitory kinase Swe1p. Mutations in three other genes (GIN4, encoding a kinase related to the Schizosaccharomyces pombe mitotic inducer Nim1p; CLA4, encoding a p21-activated kinase; and NAP1, encoding a Clb2p-interacting protein) also produce perturbations of septin organization associated with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
380
2
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 258 publications
(401 citation statements)
references
References 62 publications
(133 reference statements)
16
380
2
3
Order By: Relevance
“…Further study of two cdc42 effector-loop mutants and of the roles of Bem3p, Rga1p, and Rga2p, which are three GTPase-activating proteins (GAPs) for Cdc42p (Zheng et al, 1993;Stevenson et al, 1995;Johnson, 1999;Smith et al, 2002), has suggested that Cdc42p GTPase cycling is involved in septin-ring formation (Gladfelter et al, 2002). In particular, it was suggested that Cdc42p, like the assembly GTPase EF-Tu in protein synthesis, participates in septin-ring formation by shuttling septin complexes to the assembling ring structure (Gladfelter et al, 2002), a view that contrasts with the more common view of activated (i.e., GTP-bound) Cdc42p activating effectors in signaling pathways in a Ras-like manner (Johnson, 1999).In addition to Cdc42p, its GEF, and its GAPs, several other proteins including Bni5p, Nap1p, and the protein kinases Cla4p, Gin4p, and Elm1p are also known to be involved in formation of the normal septin ring (Cvrcková et al, 1995;Longtine et al, 1998aLongtine et al, , 2000Sreenivasan and Kellogg, 1999;Bouquin et al, 2000;Weiss et al, 2000;Lee et al, 2002). Cla4p may function in the same pathway as Cdc42p, because it is a Cdc42p effector (Cvrcková et al, 1995;Weiss et al, 2000), although it is not clear whether the interaction between Cla4p and Cdc42p is required for its role in septin organization.…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…Further study of two cdc42 effector-loop mutants and of the roles of Bem3p, Rga1p, and Rga2p, which are three GTPase-activating proteins (GAPs) for Cdc42p (Zheng et al, 1993;Stevenson et al, 1995;Johnson, 1999;Smith et al, 2002), has suggested that Cdc42p GTPase cycling is involved in septin-ring formation (Gladfelter et al, 2002). In particular, it was suggested that Cdc42p, like the assembly GTPase EF-Tu in protein synthesis, participates in septin-ring formation by shuttling septin complexes to the assembling ring structure (Gladfelter et al, 2002), a view that contrasts with the more common view of activated (i.e., GTP-bound) Cdc42p activating effectors in signaling pathways in a Ras-like manner (Johnson, 1999).In addition to Cdc42p, its GEF, and its GAPs, several other proteins including Bni5p, Nap1p, and the protein kinases Cla4p, Gin4p, and Elm1p are also known to be involved in formation of the normal septin ring (Cvrcková et al, 1995;Longtine et al, 1998aLongtine et al, , 2000Sreenivasan and Kellogg, 1999;Bouquin et al, 2000;Weiss et al, 2000;Lee et al, 2002). Cla4p may function in the same pathway as Cdc42p, because it is a Cdc42p effector (Cvrcková et al, 1995;Weiss et al, 2000), although it is not clear whether the interaction between Cla4p and Cdc42p is required for its role in septin organization.…”
mentioning
confidence: 60%
“…Mutation of the PAK-kinase gene CLA4 produces significant defects in septin organization and cell morphology (Cvrcková et al, 1995;Richman et al, 1999;Longtine et al, 2000;Weiss et al, 2000; Figure 5A). However, a bem3⌬ rga1⌬ cla4⌬ triple mutant had defects in both cell morphology ( Figure 5A) and septin organization ( Figure 5B) that were much more severe than those of either the cla4⌬ single mutant or the bem3⌬ rga1⌬ double mutant (cf.…”
Section: Defective Septin Organization In Cdc42p Gap Mutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…One set of proteins that is recruited to the septin collar in budding yeast includes the protein kinases Hsl1 and Swe1 (the S. cerevisiae homolog of Wee1 [87]) and a protein-arginine methyltransferase called Hsl7 [84][85][86] (Figure I). In response to perturbation of septin filament (or actin filament) organization, Swe1 is stabilized and, hence, its ability to phosphorylate a conserved tyrosine residue in the cyclin B-bound form of the Cdc28 cyclindependent kinase persists.…”
Section: Box 1 the Morphogenesis Checkpointmentioning
confidence: 99%
“…Septins are recruited to the nascent bud site in a Cdc42p-dependent manner, and then remain at that location as a ring around the neck of the emerging and growing bud, and finally divide into two rings at cell separation ( Figure S2A and B; for review, see Field and Kellogg, 1999;Gladfelter et al, 2001;Faty et al, 2002;Longtine and Bi, 2003). However, the septins play a variety of roles, promoting the proper activation of the B-cyclins for cell cycle progression (Barral et al, 1999;McMillan et al, 1999;Shulewitz et al, 1999;Longtine et al, 2000;Hanrahan and Snyder, 2003), maintaining a diffusion barrier between the bud and mother cortices , and recruiting cytokinetic (Bi et al, 1998;Lippincott and Li, 1998) and cell wall-synthesizing machinery (DeMarini et al, 1997) to the bud neck. To determine whether septins influence actin cable organization, we examined Tpm1p distribution in yeast with a temperaturesensitive CDC10 septin (cdc10-1) (Hartwell, 1971).…”
Section: Actin Assembly At the Bud Neck Requires The Septinsmentioning
confidence: 99%